8.1 Exponential Functions

1 / 5

# 8.1 Exponential Functions - PowerPoint PPT Presentation

8.1 Exponential Functions. ©2001 by R. Villar All Rights Reserved. Exponential Functions. Exponential Function: An equation in the form f(x) = Ca x . Recall that if 0 &lt; a &lt; 1 , the graph represents exponential decay

I am the owner, or an agent authorized to act on behalf of the owner, of the copyrighted work described.

## PowerPoint Slideshow about '8.1 Exponential Functions' - gaius

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript

### Exponential Functions

Exponential Function: An equation in the formf(x) = Cax.

Recall that if 0 < a < 1 , the graph represents exponential decay

and that if a > 1, the graph represents exponential growth

Examples: f(x) = (1/2)x f(x) = 2x

Exponential Decay

Exponential Growth

We will take a look at how these graphs “shift” according to changes in their equation...

### Take a look at how the following graphs compare to the original graph of f(x) = (1/2)x :

f(x) = (1/2)x f(x) = (1/2)x + 1 f(x) = (1/2)x – 3

Vertical Shift: The graphs of f(x) = Cax + k are shifted vertically by k units.

### Take a look at how the following graphs compare to the original graph of f(x) = (2)x :

(3,1)

(0,1)

(-2,-2)

f(x) = (2)x f(x) = (2)x – 3 f(x) = (2)x + 2 – 3

Notice that f(0) = 1

Notice that this graph

is shifted 3 units to the

right.

Notice that this graph

is shifted 2 units to the

left and 3 units down.

Horizontal Shift: The graphs of f(x) = Cax – h are shifted horizontally by h units.

### Take a look at how the following graphs compare to the original graph of f(x) = (2)x :

(0,1)

(0,-1)

(-2,-4)

f(x) = (2)x f(x) = –(2)x f(x) = –(2)x + 2 – 3

Notice that f(0) = 1

This graph

is a reflection of

f(x) = (2)x . The graph is

reflected over the x-axis.

Shift the graph of

f(x) = (2)x ,2 units to the left. Reflect the graph over the x-axis. Then, shift the graph 3 units down